A simple and practical approach to elective egg freezing to control costs and expand access to care - Raoul Orvieto; Norbert Gleicher (BMC, 2024)
Abstract Social elective egg freezing (EEF) is now widely used globally but in many countries is unaffordable to many women because of high costs and lacking insurance coverage. Efforts to reduce costs, therefore, are of importance. Surprisingly, a simple, well-defined and practical approach ensuring optimal outcomes for EEF has, however, so-far not been published. We, therefore, conducted a narrative review of the literature for relevant articles regarding the different steps of ovarian stimulation (OS) in the EEF process, in order to define such a standard protocol. This review revealed that in order to maximize oocyte yields with minimal number of OS cycles - while ensuring patient safety - a multiple-dose GnRH antagonist protocol with a daily gonadotropin dose of 300 IU appears best, unless patients demonstrate a polycystic ovarian phenotype, suggestive of likely high responses. The initial gonadotropin should be recFSH, while LH supplementation should be co-administered with the addition of GnRH antagonist. Final follicular maturation should be triggered by GnRH agonist trigger, with a dual trigger (1000-1500 IU hCG) considered for suboptimal responders to GnRH agonist trigger, optionally with Cabergoline to mitigate ovarian hyperstimulation syndrome (OHSS) in high responders.